Aplikasi Pembelajaran Algoritma Affine Cipher Dan Vigenere Cipher Menggunakan Metode Computer Assisted Instruction - Togiana, Eveline (LPPM UNIKA Santo Thomas Medan, 2018)
Learning is a process of communication between teachers and students. Cryptographic learning is very important for computer students to know the ways to secure data. Then learning is needed about data security, namely using cryptographic methods with the Affine Cipher algorithm and vigenere cipher. The Affine Cipher algorithm is a form of classical cryptography that uses the nature of substitution in the process of encoding data where the process is done by multiplying each plaintext value by a value and adding it with a shift. Vigenere Cipher algorithm is one form of classical cryptography with substitution techniques. Computer Assisted Instruction (CAI) is a computer for presenting learning material that aims to make students more active in learning material in the use of computer media. In its development Computer Assisted Instruction (CAI) has five learning system models namely tutorial models, practice models and exercises, problem solving models, simulation models, and game models, the advantages of Computer Assisted Instruction (CAI) in education can increase student motivation in learning, improve student understanding in the material presented.